2016
DOI: 10.1074/jbc.m115.669416
|View full text |Cite
|
Sign up to set email alerts
|

A Cytosolic Multiprotein Complex Containing p85α Is Required for β-Catenin Activation in Colitis and Colitis-associated Cancer

Abstract: Wnt/␤-catenin signaling is required for crypt structure maintenance. We previously observed nuclear accumulation of Ser-552 phosphorylated ␤-catenin (p␤-Cat Ser-552 ) in intestinal epithelial cells (IEC) during colitis and colitis-associated cancer. Data here delineate a novel multiprotein cytosolic complex (MCC) involved in ␤-catenin signaling in the intestine. The MCC contains p85␣, the class IA subunit of PI3K, along with ␤-catenin, 14-3-3, Akt, and p110␣. MCC levels in IEC increase in colitis and colitis-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The dysregulation of β-Catenin homeostasis is a key indicator of the hyperactive Wnt signaling (15), and β-Catenin is a mutational target in colitis-associated carcinogenesis, based on its increased expression and altered subcellular distribution (11). We have previously demonstrated a cross talk between Cld-1 and the Wnt-signaling (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dysregulation of β-Catenin homeostasis is a key indicator of the hyperactive Wnt signaling (15), and β-Catenin is a mutational target in colitis-associated carcinogenesis, based on its increased expression and altered subcellular distribution (11). We have previously demonstrated a cross talk between Cld-1 and the Wnt-signaling (6).…”
Section: Resultsmentioning
confidence: 99%
“…It was however interesting that it was β-Catenin ser552-phosphorylation that was impacted in Cld-1Tg mice when subjected to colitis. Of note, recent studies have highlighted the essential role of this signaling mechanism in colitis-associated injury/repair and colon carcinogenesis (11, 26). Our findings that the Wnt/β-Catenin Ser552 signaling was upregulated even in colon cancer cells overexpressing Cld-1 suggests an epithelial cell intrinsic effect of the upregulated Cld-1 levels upon Wnt/β-catenin signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34, 35, 36 Recent findings indicated that TBL1XR1 and β-catenin can recruit each other to Wnt target gene promoters to facilitate transcriptional activation and oncogenesis. 10 TBL1XR1 can promote the EMT of tumour cells via activating β-catenin signalling.…”
Section: Resultsmentioning
confidence: 99%
“…When the active Wnt ligand was absent, β-catenin would bind to Axin (the scaffold proteins axis inhibition protein) and APC (adenomatosis polyposis coli), and interact with GSK-3β leading to the phosphorylation of four n-terminal residues of β-catenin ( Figure 10 ). The phosphorylated β-catenin controlled by APC, GSK-3β, Axin2, and CK1 (casein kinase 1) was a target for ubiquitination and proteosomal degradation [ 65 ]. When the Wnt ligand was present, β-catenin would bind to membrane receptor frizzled (FZD) and the low-density lipoprotein receptor-related protein (LRP), leading to the cytoplasmic LRP phosphorylation by GSK-3β, which further caused the aggregation of cytoplasmic proteins, Dishevelled (Dvl) and Axin, and then the β-catenin phosphorylation and protein degradation were inhibited [ 64 ].…”
Section: Discussionmentioning
confidence: 99%